Organometallic Chalcones Functioning as Radical Traps: Observations on the Solvated Electron Reduction and the C·H2oh and C·H2cl Addition Processes. a Time-Resolved, Mechanistic Study - Godoy-Gonzalez, F; Godoy-Gonzalez, F; Maldonado-Hernandez, T; Maldonado-Hernandez, T (American Chemical Society, 2016)
The pulse radiolysis method was used to investigate reactions between organometallic chalcones derived from ferrocene, cyrhetrene, and cymantrene substituted with a phenyl (R1) or a 4′-benzo-15-crown-5 (B1) moiety and the solvated electron e−sol and two radicals. The principal spectroscopic transformations resolved with the e−sol reactions reveal that the chalcone compounds react under a diffusion controlled condition. The chromophore in the reaction product is the radical anion chalcone, −C(O)CHCH−. The kinetics of the redox processes are consistent with the formation of the radical anion in a first step, followed by an E/Z isomerization reaction in the second step. The rate of the E/Z isomerization reaction is dependent on the chalcone substituent. Reactions with C·H2OH and C·H2Cl radicals are strongly affected by the nature of the organometallic fragment. The transient spectra for the reactions between C·H2OH and C·H2Cl radicals with the phenyl-substituted chalcone show weak, broad absorption bands at λob < 400 nm. Only the ferrocenyl derivatives showed an intense absorption band with λmax = 350 nm. The C-centered radicals react with organometallic chalcones with lifetimes less than or equal to a few microseconds, and the products are assigned as adducts of the C-centered radicals to the chalcone. © 2016 American Chemical Society.